Endocytosis of simian virus 40 into the endoplasmic reticulum (The Rockefeller University Press, 1989)
The endocytosis of SV-40 into CV-1 cells we studied using biochemical and ultrastructural techniques. The half-time of binding of [35S]methionine-radiolabeled SV-40 to CV-1 cells was 25 min. Most of the incoming virus particles remained undegraded for several hours. Electron microscopy showed that some virus entered the endosomal/lysosomal pathway via coated vesicles, while the majority were endocytosed via small uncoated vesicles. After infection at high multiplicity, one third of total cell-associated virus was observed to enter the ER, starting 1-2 h after virus application. The viruses were present in large, tubular, smooth membrane networks generated as extentions of the ER. The results describe a novel and unique membrane transport pathway that allows endocytosed viral particles to be targeted from the plasma membrane to the ER.